Adolescent pregnancy: An important issue for paediatricians and primary care providers—A position paper from the European academy of paediatrics - Vieira Martins, Miguel; Karara, Nora; Dembiński, Lukasz; Jacot-Guillarmod, Martine; Mazur, Artur; Hadjipanayis, Adamos; Michaud, Pierre-André (Frontiers in Pediatrics, 2023)
Adolescent pregnancy and childbearing, remain a widespread health-related problem with potential short and long-term consequences. Comprehensive social, economic, environmental, structural, and cultural factors heavily impact on adolescents’ sexual and reproductive health and early pregnancy. Health professionals can play a pivotal role in the prevention of unplanned pregnancy. Improved access to family planning, sexuality education in the school community-based interventions and policies contribute greatly to reduce the risk of adolescent pregnancy and the adoption of respectful and responsible sexual behaviour. Additionally, health care professionals can support pregnant adolescents in making decisions under these circumstances and provide adequate health care. This review highlights actions that can guide healthcare professionals in empowering young adolescents to become more aware and capable of making informed decisions about their sexual life, health, and future.